THE ASSOCIATION BETWEEN EXPRESSION OF EPIDERMAL GROWTH FACTOR RECEPTOR WITH PRIMARY TUMOR VOLUME OF NASOPHARYNGEAL CARCINOMA - Audi Wahyu Utomo; Indah Asmara Gustarini (TALENTA PUBLISHER, 2019)
Objective: Tumor development was triggered by the excess population of the Epidermal Growth Factor Receptor (EGFR). Expression of EGFR with primary tumor volume of in patients with NPC. Expression of EGFR has a role in the increasing of metastasis, self-renewal, drug resistance and anti-apoptosis. EGFR expression associated with tumors size, positively nodules and advanced tumor stage in NPC patients. High level of EGFR expression by immunohistochemical examination associated with the development, progression and differentiation cell of tumors. Methods: Using Cross-sectional as study design. Formalin-fixed paraffin-embedded biopsy specimens were obtained. The expression of EGFR was studied with immunohistochemistry using EGFR polyclonal antibody (Bioss, USA). Assessment of the staining was performed by pathologist consultant used histoscore. The Pearson’s correlation test was used to determine the correlation between expression of EGFR and primary tumor volume of nasopharyngeal carcinoma. Statistical significance was defined as p <0.05. Result: Total samples are 19 patients. The result of EGFR expression in NPC patients with a primary tumor volume of 1-50 ml is 5 samples with a weak positive expression and 4 samples with moderate positive expression. NPC with a primary tumor volume of 51-100 ml is 2 samples of negative expression, 1 sample of weak positive expression, 3 samples with moderate positive expression and 2 samples with strong positive expression. NPC with primary tumor volume >100 ml is 1 sample weak positive expression and 1 sample strong positive expression. Statistical analysis using Pearson’s exact test was obtained p=0.047 with a correlation coefficient 0.461. EGFR expression from all of the patients there was 2 samples (10.53%) negatives, 7 samples (36.84%) weak positive, moderate positive was 7 samples (36.84%), and strong positive 3 samples (15.79%). Conclusion: There was an association between the expression of EGFR with the primary tumor volume of nasopharyngeal carcinoma.